Primary suspect - Scott, Laura, 1961- (New York : Love Inspired Books, 2018)
"When fire investigator Mitch Callahan is attacked at a crime scene, he's shocked to uncover the body of a slain ex-girlfriend--and realize someone's framing him for murder. Widowed ER nurse Dana Petrie believes Mitch is innocent, and not just because he makes her feel alive again after tragedy marred her past. But is she willing to risk everything only to love and lose again?"--Page 4 of cover.
Keywords: Nurses -- Fiction; Fire investigation -- Fiction; Man-woman relationships -- Fiction; Murder -- Fiction; Christian fiction; Romance fiction; Thrillers (Fiction)